2016
DOI: 10.1371/journal.pone.0163397
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Neutrophil to Lymphocyte Ratio Is Associated with Poor Survival in Patients with Stage I-III Non-Small Cell Lung Cancer

Abstract: BackgroundNeutrophil-to-lymphocyte ratio (NLR) has been shown to be a prognostic indicator in several types of cancer. We aimed to investigate the association between NLR and survival in surgery-treated non-small cell lung cancer (NSCLC) patients.Study DesignThis large retrospective study included 1,245 patients who underwent initial surgery for stage I–III NSCLC at The University of Texas MD Anderson Cancer Center between December 2002 and November 2010. We analyzed the relationship of NLR with clinicopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 50 publications
1
24
0
7
Order By: Relevance
“…In these three nomograms, which contain an independent nomogram exclusively for BD‐IPMN, cyst size and existence of a solid component are common predictors of malignant lesions in BD‐IPMN,8, 25, 26 and older age is also a predictor in two nomograms 8, 26. Gemenetzis et al29 included both MD‐IPMN and BD‐IPMN in a nomogram, and one of its factors predicting invasive cancer is the neutrophil‐to‐lymphocyte ratio, which has been reported to be a predictor of invasive cancer and poor prognosis in patients with various types of tumors 30, 31, 32, 33…”
Section: Prediction Of Malignant Ipmn By Nomogrammentioning
confidence: 99%
“…In these three nomograms, which contain an independent nomogram exclusively for BD‐IPMN, cyst size and existence of a solid component are common predictors of malignant lesions in BD‐IPMN,8, 25, 26 and older age is also a predictor in two nomograms 8, 26. Gemenetzis et al29 included both MD‐IPMN and BD‐IPMN in a nomogram, and one of its factors predicting invasive cancer is the neutrophil‐to‐lymphocyte ratio, which has been reported to be a predictor of invasive cancer and poor prognosis in patients with various types of tumors 30, 31, 32, 33…”
Section: Prediction Of Malignant Ipmn By Nomogrammentioning
confidence: 99%
“…Cumulative evidence has revealed that tumor-promoting in lammation contributes to cancer growth and progression by creating a tumor-promoting microenvironment, stimulates the proliferation of bronchial stem cells, and triggers the carcinogenesis of lung epithelial cell. Additionally, systematic in lammatory can not only cause tumor growth and promote tumor metastasis by activating type 2 T-assisted response, chemokines, vascular regeneration and others [4], but also responsible for reducing the effect of anti-cancer drugs and cancer-related symptoms including anorexia, cancerous pain, debilitation, cachexia [2]. In total, systematic in lammation has been shown to play an important impact on the pathogenesis and progression of NSCLC and is of great value to the aggravation and prognosis of NSCLC.…”
Section: Editorialmentioning
confidence: 99%
“…Non-small cell lung cancer (NSCLC) accounts for approximately 85% of all cases of lung cancer [1], but fewer than 15% of individuals diagnosed with NSCLC can survive for more than 5 years, which poses a great threat to the patient's life and health [2]. Recently, the incidence of lung cancer keeps dynamically growing, but more than 75% of patients at diagnosis has appeared local development or metastasis, missing the best period of surgery.…”
Section: Editorialmentioning
confidence: 99%
See 2 more Smart Citations